1972
DOI: 10.1016/s0006-3495(72)86159-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic Pressure Effects on Protein Synthesis

Abstract: The effects of high hydrostatic pressure on several phases of cell-free protein synthesis have been examined. The initial rate of polyuridylic acid (poly U)-directed synthesis of polyphenylalanine showed an apparent increase at 100 atm, above which the synthetic rate was reduced sharply with increased pressure up to 640 atm where 95% inhibition was observed. The magnitude of the inhibition of polyphenylalanine synthesis with increased pressure depended strongly on the magnesium salt concentration in the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

1974
1974
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
3
6
1
Order By: Relevance
“…The data have demonstrated that a moderate pressure load in the right ventricle elicits an early increase in protein synthesis while volume loading does not, and suggest a ventricular pressure receptor affecting protein synthesis. The latter may indeed be akin to the osmotic pressure receptor postulated in the liver (32,33) or similar to the ribosome receptor suggested earlier (31). With further increases in pressure, there is an anomalous decrease in right ventricular protein synthesis.…”
Section: Progressive Right Ventricular Hypoxiasupporting
confidence: 66%
See 1 more Smart Citation
“…The data have demonstrated that a moderate pressure load in the right ventricle elicits an early increase in protein synthesis while volume loading does not, and suggest a ventricular pressure receptor affecting protein synthesis. The latter may indeed be akin to the osmotic pressure receptor postulated in the liver (32,33) or similar to the ribosome receptor suggested earlier (31). With further increases in pressure, there is an anomalous decrease in right ventricular protein synthesis.…”
Section: Progressive Right Ventricular Hypoxiasupporting
confidence: 66%
“…Recently it has been demonstrated that alterations in hydrostatic pressure may affect protein synthesis, and a similar anomalous protein synthesis-pressure relationship has been described in subcellular systems (31). Progressive increases in hydrostatic pressures first increased and then decreased protein synthesis.…”
Section: Progressive Right Ventricular Hypoxiamentioning
confidence: 75%
“…While this communication was being prepared, an account of studies which in part parallel our work appeared (6). Although important differences do exist, our results generally substantiate and augment these findings and have already been presented in a preliminary fashion (5).…”
Section: Introductionsupporting
confidence: 85%
“…Synthesis of Phe-tRNA was strongly inhibited by pressure: formation of this intermediate decreased rapidly, and did not occur at 800 atrn or greater. This reduction was much more pronounced than that observed by Hildebrand and Pollard (6) in a crude extract and may indicate a differential sensitivity to pressure of the aminoacyl-tRNA synthetases. Furthermore, Can.…”
Section: Formation Of Aminoacyl-trna Under Pressurementioning
confidence: 49%
See 1 more Smart Citation